The Paediatric AirWay Suction (PAWS) appropriateness guide for endotracheal suction interventions. Issue 6 (November 2022) - Schults, Jessica; Charles, Karina; Long, Debbie; Brown, Georgia; Copnell, Beverley; Dargaville, Peter; Davies, Kylie; Erikson, Simon; Forrest, Kate; Harnischfeger, Jane; Irwin, Adam; Kendrik, Tina; et al.
Abstract: Background/objective: Endotracheal suction is an invasive and potentially harmful technique used for airway clearance in mechanically ventilated children. Choice of suction intervention remains a complex and variable process. We sought to develop appropriate use criteria for endotracheal suction interventions used in paediatric populations. Methods: The RAND Corporation and University of California, Los Angeles Appropriateness Method was used to develop the Paediatric AirWay Suction appropriateness guide. This included defining key terms, synthesising current evidence, engaging an expert multidisciplinary panel, case scenario development, and two rounds of appropriateness ratings (weighing harm with benefit). Indications (clinical scenarios) were developed from common applications or anticipated use, current practice guidelines, clinical trial results, and expert consultation. Results: Overall, 148 (19%) scenarios were rated as appropriate (benefit outweighs harm), 542 (67%) as uncertain, and 94 (11%) as inappropriate (harm outweighs benefit). Disagreement occurred in 24 (3%) clinical scenarios, namely presuction and postsuction bagging across populations and age groups. In general, the use of closed suction was rated as appropriate, particularly in the subspecialty population ' patients with highly infectious respiratory disease '. Routine application of 0.9% saline for nonrespiratory indications was more likely to be inappropriate/uncertain than appropriate. Panellists preferred clinically indicated suction versus routine suction in most circumstances. Conclusion: Appropriate use criteria for endotracheal suction in the paediatric intensive care have the potential to impact clinical decision-making, reduce practice variability, and improve patient outcomes. Furthermore, recognition of uncertain clinical scenarios facilitates identification of areas that would benefit from future research.